Power of Brand Name Characteristics on Leisure Shopping - Glodiya Fernando, N.I.; Shivany, S. (Research gate, 2017)
In the essence, customers feel that going shopping is one of their favorite leisure activities. Shopping enjoyment as a consumer’s personality trait that finds shopping more enjoyable and experiences greater shopping pleasure than other consumers experience. Also Brand character enriches brand image. It is an expression of brand that leads to cognitive or emotional associations in the consumer’s mind. Brand associations consist of all the thoughts, feelings, experiences, beliefs and so on associated to the brand. This study is to identify the influence of brand name characteristics on leisure shopping in Mannar. It has not been proven by any researchers that brand name characteristics are related to leisure shopping. This study will helpful to producers by providing a clear background about how producers adopt brand name strategies to provide a better value to their customers in their leisure time. The main purpose of this study is to examine the impact of brand name characteristics on leisure shopping, among the people in Mannar, Sri Lanka. The study showed distinctive results for the relationship between brand name characteristics dimensions and leisure shopping. Among these variables, Distinctive, Use of repetitive sounds have the significant association with customer satisfaction. Whereas Distinctive brand name characteristics highly impact leisure shopping. Overall, brand name characteristics significantly associated with leisure shopping. Finding shows that brand name characteristics can be enriched to improve the leisure shopping.
Keywords: Brand; Brand Name Characteristics; Leisure; Leisure Shoppers; Leisure Shopping.